Analisis Green Growth Petani Gambir di Kecamatan Bukik Barisan Kabupaten Lima Puluh Kota Sumatera Barat - Nur Sindy Oktavia; Fery Andrianus; Maryanti Maryanti (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2022)
Green growth strategies need attention to various aspects that can support strategy implementation. Green growth is environmentally friendly economic growth aimed at alleviating poverty along with the reduced availability of natural resources and climate change. One of the most important commodities in the plantation sub-sector which includes green growth is gambier (Uncaria Gambier Roxb). This study aimed to analyze the gambier production process by applying green growth analysis in Bukik Barisan District using quantitative descriptive analysis through questionnaires and interviews distributed in Bukik Barisan District, Lima Puluh Kota Regency. The results of this study indicated that by using two production processes, such as the planting process starts from the land clearing process, seeding, planting, maintenance, picking gambier leaves and processing. The post-harvest gambier production process is carried out from boiling gambier leaves, pressing, precipitation, draining, printing and drying which shows that gambier plants are green growth plants or eco-friendly plants.